2021
DOI: 10.1029/2021ja029651
|View full text |Cite
|
Sign up to set email alerts
|

Prompt Penetration and Substorm Effects Over Jicamarca During the September 2017 Geomagnetic Storm

Abstract: We used reanalyzed Jicamarca radar measurements to study the response of equatorial ionospheric electrodynamics and spread F during the main phase of the large September 2017 geomagnetic storm. Our observations near dusk on 7 September show very large upward drifts followed by a large short‐lived downward drift perturbation that completely suppressed the lower F region plasma irregularities and severely decreased the backscattered power from the higher altitude spread F. We suggest that this large short‐lived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Geomagnetic storms may occur during the southward polarity of the interplanetary magnetic field (Bz) that manipulates the regular equatorial electric fields to trigger pre-reversal enhancements (PREs) to seed the generation and development of plasma bubbles [2][3][4]. Additionally, the substorms formed at the polar latitudes can alter the equatorial electric field during the recovery of geomagnetic storms resulting in an increase or decrease in the scintillation activity [5][6][7][8]. Generally, the ionospheric electrodynamics during the geomagnetic storms are affected by two sources: (1) the short-lived penetrating electric fields from high to low latitudes corresponding to the southward turning of the interplanetary magnetic field Bz to drive eastward (westward) the polarized disturbances at the day and evening sectors (nightside) [9][10][11][12]; and (2) the disturbance dynamo electric fields (DDEFs) resulting from the changes in neutral winds that develop a few hours after the onset of the storm and usually last for several hours via thermospheric wind dynamo action, often dominating in the recovery phase [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geomagnetic storms may occur during the southward polarity of the interplanetary magnetic field (Bz) that manipulates the regular equatorial electric fields to trigger pre-reversal enhancements (PREs) to seed the generation and development of plasma bubbles [2][3][4]. Additionally, the substorms formed at the polar latitudes can alter the equatorial electric field during the recovery of geomagnetic storms resulting in an increase or decrease in the scintillation activity [5][6][7][8]. Generally, the ionospheric electrodynamics during the geomagnetic storms are affected by two sources: (1) the short-lived penetrating electric fields from high to low latitudes corresponding to the southward turning of the interplanetary magnetic field Bz to drive eastward (westward) the polarized disturbances at the day and evening sectors (nightside) [9][10][11][12]; and (2) the disturbance dynamo electric fields (DDEFs) resulting from the changes in neutral winds that develop a few hours after the onset of the storm and usually last for several hours via thermospheric wind dynamo action, often dominating in the recovery phase [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The space weather event of 6-10 September 2017 was a complex event associated with multiple X-and M-class solar flares and severe geomagnetic storms, when the GNSS signals witnessed pronounced post-sunset scintillations due to strong EPB irregularities. The occurrences of plasma density irregularities, their drifting characteristics, and the mechanisms responsible for this occurring over different longitude sectors during the storm of September 2017 have been widely investigated in the earlier literature [3,8,[44][45][46][47][48][49][50][51]. From the investigation of the topside ionospheric conditions during this particular storm period, with uplooking GNSS TEC from the observations retrieved from TerraSAR-X, GRACE, Swarm, and MetOp-A, and the in situ electron density (Ne) from the Swarm satellite, Jimoh et al [50] reported night-time ROTI enhancements across a wide latitudinal range during the main phase of the storm.…”
Section: Introductionmentioning
confidence: 99%
“…Since two solar flares X2.2 and X9.3 erupted over the active region 2673 on 6 September 2017, a strong geomagnetic storm with double main phases was generated on 8 September 2017 (Yamauchi et al., 2018). Based on the observations derived from GNSS receivers, radars, and ionosondes, numerous studies have investigated the complex responds of ionosphere at different latitudes to this strong storm (Aa et al., 2018; Fejer et al., 2021; Habarulema et al., 2020; Li et al., 2018; Xiong et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…3 of 13 the complex responds of ionosphere at different latitudes to this strong storm (Aa et al, 2018;Fejer et al, 2021;Habarulema et al, 2020;Li et al, 2018;Xiong et al, 2019).…”
Section: Strong Geomagnetic Storm On 8 September 2017mentioning
confidence: 99%
“…giving rise to the so-called "Region 2" currents near the equatorial plane in the ionosphere and creating a partial dusk-to-dawn electric field that tends to shield the near-Earth region opposing the convection in the inner magnetosphere. These shielding electric fields immediately alter the electrodynamics over low-latitude regions significantly (Abdu et al 2009a;2012;2016;Fejer et al 2021;Kelley et al 1979a;Kikuchi et al 2008;Peymirat et al 2000). This aspect must be considered every time a space weather evaluation is carried out but may be taken into account indirectly through other parameters to be discussed later.…”
Section: The Geomagnetic Field and Geomagnetic Stormsmentioning
confidence: 99%